Postharvest deterioration of tomato and it’s management strategies: a review - Rai, Ritesh Kumar; Singh , Pooja (Journal of Postharvest Technology, 2022)
Tomato (Lycopersicon esculentum Mill.) is an important vegetable crop cultivated and consumed worldwide. Due to inadequate postharvest  handling in the field, transit and storage, pathogenic mycoflora leads to processes of rot with consequent loss of products up to 30-40% in  developing countries. Several studies regarding the postharvest decay of tomato and prevention of loss of quality have been studied; various  methods such as physical, chemical, biological and botanical have been carried out. This review aims to explore several postharvest fungal  diseases and physiological disorders of tomato along with their management strategies.
Keywords: Tomato; postharvest diseases; management,; , physical,; chemical; botanical